The Greeks in Australia - Tamis, A. M. (Anastasios M.) (Sociology of race and ethnicity., 2005)
"The Greeks have made an enormous contribution to Australian cultural and social life, and this book tells their story. Beginning with an examination of the conditions in Europe that led to migration, it details the role of the Greek people in Australian settlement, the two large waves of Greek migration in the nineteenth and twentieth centuries, and the ways in which the Greeks have maintained a solid sense of Greek cultural expression. Numbering approximately half a million, the Greek community in Australia comprises the second-largest ethnic minority after the Italians